John Wood 1: The Undervalued Cartographer. (August 2014) - Robson, Brian
<x content-type="archive" xml:space="preserve">Abstract</x> Very little is known about the work or life of the 19th-century cartographer John Wood. He is generally thought to have worked principally on producing plans of Scottish towns, but this research has now identified some 150 of his plans covering towns across much of England and Wales as well as Scotland. It throws new light on his life and on the comprehensive hands-on nature of his involvement with all the stages of producing this astounding output. His cartographic achievement warrants his being far more widely recognized in the annals of British cartography.